Peran Fatwa Muhammadiyah tentang Hukum Merokok dalam Sikap, Norma Subjektif, dan Kontrol Perilaku terhadap Perilaku Merokok - Muh Nur Akhsin Ridho; Evi Martha (Politeknik Kesehatan Tanjung Karang, 2020)
Muhammadiyah has issued a fatwa that smoking is haram. Nevertheless, there are still muhammadiyah residents who remain to smoke. This thesis discusses the role of fatwa Muhammadiyah about haram smoking law against employee smoking behavior. The purpose of this research was to know the role of Muhammadiyah fatwa about smoking law in attitude, subjective norm, behavior control, and intention toward smoking behavior of employees of Da’wah Muhammadiyah Center. This research was qualitative and choosing a location at the Muhammadiyah Da'wah Center Jakarta. The number of informants was 14 people. Informants were obtained by purposive and data collection techniques through observation, document review, and in-depth interviews. The results showed that for smokers informants, attitudes and subjective norms did not contribute to smoking cessation behavior, while behavior controls play a role in smoking cessation behavior. For non-smoking informants, attitudes, subjective norms, and behavioral controls play a role in non-smoking behaviors. Similarly for ex-smoker informants, attitudes, subjective norms, and behavioral controls play a role in committed non-smoking behaviors. It was suggested to the Muhammadiyah Central Executive to improve the fatwa status of smoking law into Muhammadiyah's decision to be more binding organizationally and for Muhammadiyah Da'wah Center to be a role model of implementation fatwa smoking law in Muhammadiyah.